The guidelines for designing mobile application interfaces to create an efficient user experience (Damascus University Journal for engineering sciences, 2022)
Interface design is arguably one of the most important issues in the development of mobile applications. Mobile users often suffer from the poor interface design that seriously hinders the usability of those mobile applications. The major challenge in the interface design of mobile applications is caused by the unique features of mobile devices, such as small screen size, low resolution, and inefficient data entry methods. Therefore, there is a pressing need of theoretical frameworks or guidelines for designing effective and user-friendly interfaces for mobile applications. Based on application development processes, this paper proposes a novel framework for the design of effective mobile interfaces. This framework consists of four major components, namely information presentation, data entry methods, mobile users, and context. it also provides a set of practical interface design guidelines and some insights into what factors should be taken into consideration while designing interfaces for mobile applications.
Keywords: Interface; user-centered design; mobile application; wireless environment